VALZ‐Pilot: High‐dose valacyclovir treatment in patients with early‐stage Alzheimer's disease. Issue 1 (14th March 2022) - Weidung, Bodil; Hemmingsson, Eva‐Stina; Olsson, Jan; Sundström, Torbjörn; Blennow, Kaj; Zetterberg, Henrik; Ingelsson, Martin; Elgh, Fredrik; Lövheim, Hugo
Abstract: Introduction: Herpes simplex virus (HSV) may be involved in Alzheimer's disease (AD) pathophysiology. The antiviral valacyclovir inhibits HSV replication. Methods: This phase‐II pilot trial involved valacyclovir administration (thrice daily, 500 mg week 1, 1000 mg weeks 2–4) to persons aged ≥ 65 years with early‐stage AD, anti‐HSV immunoglobulin G, and apolipoprotein E ε4. Intervention safety, tolerability, feasibility, and effects on Mini‐Mental State Examination (MMSE) scores and cerebrospinal fluid (CSF) biomarkers were evaluated. Results: Thirty‐two of 33 subjects completed the trial on full dosage. Eighteen percent experienced likely intervention‐related mild, temporary adverse events. CSF acyclovir concentrations were mean 5.29 ± 2.31 μmol/L. CSF total tau and neurofilament light concentrations were unchanged; MMSE score and CSF soluble triggering receptor expressed on myeloid cells 2 concentrations increased ( P  = .02 and .03). Discussion: Four weeks of high‐dose valacyclovir treatment was safe, tolerable, and feasible in early‐stage AD. Our findings may guide future trial design.